Lung Nodule and Pulmonary Fibrosis at First Evaluation in Smoker Undergoing a Smoking Cessation Program - Pezzuto, Aldo; Tammaro, Antonella; Salerno, Gerardo; Borro, Marina; Carico, Elisabetta (Global Journal of Respiratory Care, 2022)
Smoking is the most significant avoidable risk factor. Responsible for a wide range of diseases such as cardiovascular diseases and acute or chronic respiratory diseases. It is frequently associated with interstitial pulmonary diseases and notably, it can be a cause of idiopathic pulmonary fibrosis. In this report, lung nodules and idiopathic pulmonary fibrosis were presented in a heavy smoker.